2019
DOI: 10.3389/fpsyg.2019.01912
|View full text |Cite
|
Sign up to set email alerts
|

Goal Preferences, Affect, Activity Patterns and Health Outcomes in Women With Fibromyalgia

Abstract: Some motivational models understand health behavior as a result of the interaction between goal preferences and mood. However, this perspective has not been explored in fibromyalgia. Furthermore, in chronic pain, it has only been explored with regard to negative affect. Thus, our aims were: (1) to develop a Spanish version of the Goal Pursuit Questionnaire (GPQ); (2) to explore the relationships between goal preferences and health outcomes, testing the moderator role of affect and the mediating role of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 60 publications
5
26
2
Order By: Relevance
“…The findings of this study are generally supportive of motivational accounts of activity patterns in people with chronic pain (Van Damme, 2014; Van Damme and Kindermans, 2015;Karoly, 2018) and previous research demonstrating that the context of a goal pursuit episode is associated with activity patterns (Karsdorp et al, 2010;Karsdorp and Vlaeyen, 2011;Schrooten et Van Damme et al, 2012;Pastor-Mira et al, 2019). The most consistent determinants of motivation to conserve resources and sedentary time in this study were goal striving and perceived demands.…”
Section: Relationship To Past Researchsupporting
confidence: 87%
“…The findings of this study are generally supportive of motivational accounts of activity patterns in people with chronic pain (Van Damme, 2014; Van Damme and Kindermans, 2015;Karoly, 2018) and previous research demonstrating that the context of a goal pursuit episode is associated with activity patterns (Karsdorp et al, 2010;Karsdorp and Vlaeyen, 2011;Schrooten et Van Damme et al, 2012;Pastor-Mira et al, 2019). The most consistent determinants of motivation to conserve resources and sedentary time in this study were goal striving and perceived demands.…”
Section: Relationship To Past Researchsupporting
confidence: 87%
“…In explaining this inconsistency, different variables have been analyzed in previous studies. The concept of goal, as a variable inherent to psychological flexibility [ 7 , 13 ], has been incorporated [ 25 ], showing that preference for pain avoidance goals has been consistently associated with pain and disability through different activity patterns, especially with regards to task-contingent persistence, excessive persistence and activity avoidance patterns. Other studies have studied the relationship between activity patterns and goal management strategies while also considering the roles of affectivity and optimism [ 15 ], showing that the latter can be associated with persistence, commitment to new goals, and flexible goal management, and is associated with persisting in finishing tasks despite pain, and can also show infrequent avoidance behavior when pain is anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same line, Esteve et al [ 20 ] incorporated the goal orientation of patterns as a differential characteristic that can define their adaptive or maladaptive character (i.e., three pacing patterns, each of which is associated with a single goal (conserving energy for valued activities, increasing activity levels, and reducing pain)). Finally, recent studies have pointed out the validity of the psychological flexibility model in the relationship between activity patterns and certain disease outcomes, highlighting the role of both contextual (i.e., pain intensity [ 23 ]) and personal variables associated with one’s values (i.e., perfectionism [ 24 ], goal preferences [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%
“…They studied patients with stroke [ 32 ], depression [ 33 ] and vulvodynia [ 34 ], and suggested that associations with motivation, behaviour change and self-efficacy could be possible explanations. One study has found strong links between goal preferences and activity patterns for patients with widespread pain, and concluded that reinforcing achievement goals was recommended to improve chronic pain adaptation for patients with fibromyalgia [ 35 ]. Together with our findings, this shows there are associations between goal setting and outcomes for different patient groups and that this might be related to factors such as motivation, behaviour change and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%